Using Augmented Reality Flashcards To Improve English Vocabulary Mastery For Children Aged 4-5 Years - Hafidah, Ruli; Yusuf, Munawir; Subagya, Subagya (PIAUD Universitas Islam Negeri Sunan Kudus, 2022)
Mastery of English vocabulary is an important part of early childhood English learning in the industrial revolution 4.0 era. The use of digital learning media such as augmented reality flashcards is also needed as a way to teach English to early childhood who are now accustomed to the use of advances in digital technology. The purpose of this study was to improve the mastery of English vocabulary in children aged 4-5 years by using augmented reality flashcards. This research was conducted in August-September 2022. This research is a classroom- action research using Kurt Lewin's model which consists of 3 cycles. Each cycle consists of planning, acting, observing, and reflecting. Data collection techniques use observation and documentation. Data analysis uses the Miles and Huberman model for qualitative data and simple statistics (percentages) for quantitative data. The subjects of this research are all children aged 4-5 years at Marsudisiwi Kindergarten, Laweyan Surakarta, totaling 20 children. The results show that there was an increase in children's English vocabulary mastery from cycle 1 by 35% and increased to 85% at the end of cycle 3 for the very well-developed category (BSB). The increase was also seen from the number of vocabulary that the children acquired, the correct pronunciation of the given vocabulary, and the ability to distinguish the meaning of one word from another.